O N400 como medida de avaliação do grau de relacionamento entre estímulos equivalentes - Ryan Ríguel Barbosa do Espirito Santo (2017)
The present study aimed to use a measure of the N400 component to evaluate the overtraining effect on the degree of relationship between stimuli in equivalence class. Two groups of participants, named Overtraining and Regular, were submitted to a Matching to Sample procedure in which conditional relations were taught between stimuli sets composed by abstract figures. The training procedure for both groups was different only related to the number of the baseline trials, in a way that participants in the Overtraining Group were exposed to twice the number of baseline trials when compared to participants in the Regular Group. Fifteen participants from each group achieved at least 83% of correct responses in the equivalence test trials and were considered eligible to perform the priming semantic task. In this task, pairs of stimuli from same class and pairs of stimuli from different classes were presented in sequence way while electrodes captured and recorded the participant's neural activity. Based on the literature, only pairs of stimuli of the different class should produce a larger N400 component than pairs of stimuli of the same class. In addition, we also investigate a possible modulatory effect in the occurrence of N400 component related to the number of baseline trials. Based on permutation test results, significant differences were not find comparing the wave amplitudes of pairs of stimuli of the same class and pairs of stimuli of the different class for both groups. However, visual inspection of the wave amplitudes for participants in Regular Group allows to detect greater difference between pairs of stimuli of the same class and pairs of stimuli of the different class when compared to the wave amplitudes for participants in Overtraining Group. These results were discussed in terms of variables potentially involved in N400 modulation, such as the amount baseline trials, the use of stimuli with pre-experimental meaning and, also, the occurrence of control by rejection.